2015
DOI: 10.1177/0148607114565245
|View full text |Cite
|
Sign up to set email alerts
|

Thiamin in Clinical Practice

Abstract: Thiamin is a water-soluble vitamin also known as vitamin B1. Its biologically active form, thiamin pyrophosphate (TPP), is a cofactor in macronutrient metabolism. In addition to its coenzyme roles, TPP plays a role in nerve structure and function as well as brain metabolism. Signs and symptoms of thiamin deficiency (TD) include lactic acidosis, peripheral neuropathy, ataxia, and ocular changes (eg, nystagmus). More advanced symptoms include confabulation and memory loss and/or psychosis, resulting in Wernicke'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(162 citation statements)
references
References 122 publications
(262 reference statements)
0
153
0
9
Order By: Relevance
“…Clinical practise publications related to nutritional supplementation state that patients with suspected or at risk of developing TD should be provided with thiamine [50][51][52]. Malnutrition (starvation or reduced intake, increased loss or impaired absorption), alcoholism, bariatric surgery, refeeding, congestive heart failure, lactic acidosis, neuropathy, renal failure with dialysis and the critically ill are all risk factors for the development of TD.…”
Section: Physiology Of Thiaminementioning
confidence: 99%
See 1 more Smart Citation
“…Clinical practise publications related to nutritional supplementation state that patients with suspected or at risk of developing TD should be provided with thiamine [50][51][52]. Malnutrition (starvation or reduced intake, increased loss or impaired absorption), alcoholism, bariatric surgery, refeeding, congestive heart failure, lactic acidosis, neuropathy, renal failure with dialysis and the critically ill are all risk factors for the development of TD.…”
Section: Physiology Of Thiaminementioning
confidence: 99%
“…The transketolase activation test, or transketolase activity assay, and the pyrophosphate effect test are both indirect methods which monitor the status of TPP. Liquid chromatographic techniques, with a range of separation and detection methods, are direct methods of quantification and are the most commonly described [45,52,111].…”
Section: Analyticalmentioning
confidence: 99%
“…It also plays an important role in muscle contraction, nerve impulse conduction, and glucose absorption by the nervous system. 37 The brain stem, the cerebellum and the brain's limbic system are highly sensitive to vitamin B1 deficiency (pseudohypoxia), and its pathophysiology is similar to a continuous oxygen deprivation. 38 An incorrect vitamin B1 supplementation in soy-based formula showed that thiamin deficiency in infants causes encephalopathy, neuropathy, visual alterations, and death.…”
Section: Vitamin B1mentioning
confidence: 99%
“…También juega un papel importante en la contracción muscular, la conducción de las señales nerviosas y la absorción de glucosa por parte del sistema nervioso. 37 El tallo cerebral, cerebelo y sistema límbico del cerebro son muy sensibles a su deficiencia (pseudohipoxia), y la fisiopatología es similar a una privación continua de oxígeno. 38 La suplementación errónea de vitamina B1 en fórmulas lácteas a base de soja mostró que la deficiencia de tiamina en los lactantes producía encefalopatías, neuropatías, alteraciones oftalmológicas y muerte.…”
Section: Vitamina B1unclassified